Analisis Kelayakan Usahatani Padi Sawah di Kelurahan Pulutan, Kecamatan Sidorejo, Kota Salatiga, Jawa Tengah - Jestin, Oktavina Herianti; Simamora, Liska (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Rice is the main crop in agriculture which is one of the food crop commodities that support approximately 95% of Indonesian consumption. There are two types of rice cultivation in Indonesia, namely: paddy rice and field rice. One of the problems that occur to farmers is the price of pesticides, fertilizer prices, and rental prices for equipment that are too expensive, as well as the uncertain price of seeds. This study aims to 1). To determine the production cost, revenue, and income of paddy rice farming in Pulutan Village, Sidorejo Subdistrict, Salatiga City, Central Java, 2). To know the R/C ratio of paddy rice farming in Pulutan Village, Sidorejo Subdistrict, Salatiga City, Central Java. The research analysis used descriptive quantitative method. The data analysis used was the analysis of production cost, income, revenue, and R/C ratio. A total of 10 respondents who were taken had special characteristics, namely the status of own land ownership. The results showed that the average expenditure of paddy rice farming in Pulutan Village, Sidorejo District amounted to Rp 3,501,133/ha/growing season. The average revenue received by farmers amounted to Rp 9,243,000/ha/growing season, the average farmer's income amounted to Rp 5,741,867/ha/ growing season, and the R/C ratio value is Rp 2.64. Where this value means that farming is feasible.